INFORMATION SYSTEM FOR MEASUREMENT, TRANSMISSION AND PROCESSING OF PARAMETERS OF HYBRID POWER PLANTS - Sineglazov, V. M.; Kopaniev, V. О. (Electronics and Control Systems, 2018)
In this paper a two-tier system for tracking critical parameters of hybrid power plants, such as generated power, generator current, rotational speed, and battery charge level is considered. The proposed system refers to the online display of the power usage of solar energy as a renewable energy. This paper describes an experimental investigation of wireless monitoring and control of smart microgrid prototype. Using Blynk cloud application its possible to track parameners of hybrid solar systems in real-time. The prototype can be implemented using different communication protocols based on technical requirements such as security, data rates, coverage area and type of application.